1988
DOI: 10.5935/0305-7518.19880016
|View full text |Cite
|
Sign up to set email alerts
|

Chromosome aberrations and sister chromatid exchanges (SCEs) in peripheral blood lymphocyte cultures of untreated leprosy patients

Abstract: Summary The frequencies of various chromsome aberrations and sister chroma tid exchanges (SCEs) were studied in blood lymphocyte cultures of untreated leprosy patients. The frequency of chromosome aberrations was significantly higher in lepromatous (P Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1990
1990
2018
2018

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 1 publication
0
2
0
Order By: Relevance
“…Although Gopal et al (1999), who suggested that endo/ exotoxin released by Mycobacterium tuberculosis act as chemical mutagens in generating CA in affected individual. Other similar infections caused by Mycobacterium Lepra [30] and number of viruses, including A and B hepatitis [31] were demonstrated to cause different CAs in human lymphocytes. These abnormalities may involve the autosomes, sex chromosomes, or both.…”
Section: Eta Effect On Chromosomal Aberrations (Cas)mentioning
confidence: 99%
“…Although Gopal et al (1999), who suggested that endo/ exotoxin released by Mycobacterium tuberculosis act as chemical mutagens in generating CA in affected individual. Other similar infections caused by Mycobacterium Lepra [30] and number of viruses, including A and B hepatitis [31] were demonstrated to cause different CAs in human lymphocytes. These abnormalities may involve the autosomes, sex chromosomes, or both.…”
Section: Eta Effect On Chromosomal Aberrations (Cas)mentioning
confidence: 99%
“…These studies have not ruled out the possible role of M. leprae as an additional clastogenic agent. Recently we have shown, for the first time, a significant * Present address and address for offprint requests': Patna Women's College, Bailey Road, Patna-800 001, Bihar, India genotoxic effect of this bacterium in terms of the induced frequency of chromosome aberrations and SCEs in untreated leprosy patients, an effect shown to depend on the form of leprosy (D'Souza and Thomas 1988).…”
Section: Introductionmentioning
confidence: 99%